Hubungan Berat Badan Lahir, Status Imunisasi, dan Riwayat Penyakit Infeksi dengan Kejadian Stunting pada Balita di Puskesmas Kassi-Kassi Kota Makassar - Tiara Putri Ramli; Darmawansyih; Andi Alifia Ayu Delima (Universitas Islam Negeri Alauddin Makassar, 2023)
Stunting is a chronic condition in which measurement of the Body Length for Age (PB/A) or Height for Age (TB/A) with values in the anthropometric table <-2SD according to international references. The specific objective of this study was to determine the relationship between birth weight, immunization status, history of diarrheal infection and history of Acute Respiratory Disease with the incidence of stunting in toddlers in the Kassi-Kassi Health Center area. The research design used was analytic observational with a cross-sectional approach. The population in this study were toddlers within the scope of work of the Kassi-Kassi Health Center; using a purposive sampling technique according to the inclusive criteria, we obtained 251 toddlers. We found that there was a relationship between birth weight (p-value 0.000), immunization status (p-value 0.000), and history of infectious diarrheal disease with the incidence of stunting (p-value 0.023). Next, there was no relationship between a history of acute respiratory disease and the incidence of stunting (p-value 0.551) in toddlers at the Kassi-Kassi Health Center.